Pengaruh Film Capernaum sebagai Media Belajar Terhadap Sikap Tanggung Jawab Ekonomi - Rabina Talia; Supriyadi; Hafifi (Indo Publishing, 2025)
This research aims to explore the influence of the film Capernaum (2018) as a learning medium on students’ sense of economic responsibility. The film was chosen due to its realistic portrayal of children living in extreme poverty with limited access to education, making it a relevant tool to foster empathy and economic awareness among adolescents. The study uses a qualitative approach with an intrinsic case study design, focusing on students from SMK Persada Husada Indonesia. Data were collected through in-depth interviews, focus group discussions (FGDs), direct observations, documentation, and data triangulation to enhance the validity and depth of the findings. A total of ten students participated in the data collection process, but only three key respondents were selected for detailed analysis based on their depth of understanding regarding the research theme. The results indicate that Capernaum effectively raises students' awareness about economic responsibility, reflected in increased concern for family welfare, motivation for independence, and a stronger sense of not wanting to become an economic burden. The main character, Zain, serves as a powerful representation of resilience and the drive to survive amidst hardship, leaving a strong emotional impact on students. The film proves to be an effective educational medium by delivering moral messages through compelling visuals and emotional narratives.